Reviving the Transcriptome Studies: An Insight Into the Emergence of Single-Molecule Transcriptome Sequencing - Wang, Bo; Kumar, Vivek; Olson, Andrew; Ware, Doreen (Frontiers in Genetics, 2019)
Advances in transcriptomics have provided an exceptional opportunity to study functional implications of the genetic variability. Technologies such as RNA-Seq have emerged as state-of-the-art techniques for transcriptome analysis that take advantage of high-throughput next-generation sequencing. However, similar to their predecessors, these approaches continue to impose major challenges on full-length transcript structure identification, primarily due to inherent limitations of read length. With the development of single-molecule sequencing from PacBio, a growing number of studies on the transcriptome of different organisms have been reported. Single-molecule sequencing has emerged as advantageous for comprehensive genome annotation including identification of novel genes/isoforms, long non-coding RNAs and fusion transcripts. This approach can be used across a broad spectrum of species to better interpret the coding information of the genome, and facilitate the biological function study. We provide an overview of single-molecule sequencing platform and its diverse applications in various biological studies, and our perspective on the challenges associated with the transcriptome studies.